Mushroom pest and disease control : - Fletcher, John T. (Manson Publishing, 2008)
This book covers all aspects of mushroom pest and pathogen management on the farm and reflects practices in the highly mechanized production of mushrooms worldwide. The book menttions the changes in the industry such as environmental and biological controls, avoidance of pollution and reduced use of pesticides and how these changes influence the incidence of pest and disease